PEDAGOGICAL CONTENT KNOWLEDGE FOR TEACHING ENGLISH - Bararah Ibrahim (English Education Journal, 2016)
This research was conducted to find out how well English teachers in Banda Aceh displayed Pedagogical Content Knowledge (PCK) in teaching English and how they developed their knowledge of teaching. This research was a classroom research and the focus of the analysis was knowledge of the subject, teaching strategies and knowledge of learners’ conceptions. The participants were four English teachers (Betty, Dina, Aminah and Cut - pseudonyms), each from a different junior high school. They teach second grade ESL students. The instruments used for collecting the data were observation sheets and interview guides. The results from the study show that the teachers each had their own strengths and weaknesses in teaching English. The four participating teachers taught different topics and they showed dissimilarity in displaying PCK. Betty and Dina had more subject matter knowledge compared Aminah and Cut. For teaching strategy, Aminah, Cut, and Dina used a telling or lecture method whereas Betty used a Grammar Translation Method to teach her students to learn to understand spoken English. In the last trait analyzed, these four teachers had limited knowledge of how to identify the conceptions of learners even though they had had many years’ experience as English teachers and had often observed other colleagues. The differences in teaching knowledge amongst the sample teachers could be caused by many factors such as different methodologies used, different teaching experiences, different marital status, and different language backgrounds of the students. This study shows that these teachers still needed to improve their PCK.